Effect of environmental temperature and inoculants on the fermentation of alfalfa and forage sorghum silages - Bolsen, K.; Laytimi, A.; Nuzback, L.; Hart, R. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
The inoculants, TriLac ®and Ecosyl® increased the rate and efficiency of the ensiling process in both high (50%) and low (32.5%) dry matter alfalfa, regardless of temperature. In both alfalfa trials, the inoculated silages had significantly lower pH, acetic acid, ethanol, and ammonia-nitrogen values and higher lactic acid values than their control counterparts. The inoculants worked equally well when fermentation was at 60 or 90 F. Although similar effects were obtained with forage sorghum, the differences were not as pronounced as those for the alfalfa silages.
Keywords: Beef; Alfalfa; Sorghum silage; TriLac®; Ecosyl®